PENGARUH KUALITAS LAYANAN, PENANGANAN KELUHAN DAN KEPUASAN NASABAH TERHADAP LOYALITAS (Students' Journal of Economic and Management, 2013)
Banking industry has realized that customers today not only consider the factor of interest or completeness of the sophistication and features of a banking product, but is currently being sought by the customer is the value (value) to be derived from what is offered by the bank, so that the will eventually be willing to be a loyal customer. The purpose of this study was to analyze the effect of service quality, complaint handling and customer satisfaction on customer loyalty Simpedes savings on PT. BRI (Persero) Unit Truko Kendal. Data used in this study is primary data is data obtained directly from the original source. While the techniques used for data collection using questionnaire by asking a number of written questions used to obtain information and respondent. Population in this research is saving customers Simpedes PT. Bank BRI Unit Truko bejumlah Kendal in 2011 that as many as 4,552 customers. Based Slovin formula obtained a sample of 98 people. Sampling technique using convenience sampling or sample selected with ease. Test tool in this study using multiple linear regression. Analysis results can be concluded that: Service quality has a positive effect on customer loyalty acceptable. The better the quality of services provided, it will increase customer loyalty. Handling customer complaints positive effect on customer loyalty acceptable. The faster handling customer complaints are resolved, it will increase customer loyalty. Customer satisfaction has a positive effect on customer loyalty acceptable. Increasingly customers are satisfied, then the customer loyalty will increase quality of service, handling customer complaints and customer satisfaction together a positive effect on customer loyalty Keywords: Quality of service, handling customer complaints, customer satisfaction and customer loyalty